2011
DOI: 10.1152/ajprenal.00247.2010
|View full text |Cite
|
Sign up to set email alerts
|

Counteracting vasopressin-mediated water reabsorption by ATP, dopamine, and phorbol esters: mechanisms of action

Abstract: Water homeostasis is regulated by a wide variety of hormones. When in need for water conservation, vasopressin, released from the brain, binds renal principal cells and initiates a signaling cascade resulting in the insertion of aquaporin-2 (AQP2) water channels in the apical membrane and water reabsorption. Conversely, hormones, including extracellular purines and dopamine, antagonize AVP-induced water permeability, but their mechanism of action is largely unknown, which was investigated here. Addition of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 42 publications
(69 reference statements)
0
20
0
Order By: Relevance
“…35 Briefly, male SpragueDawley rats were anesthetized and euthanized by decapitation. Kidneys were quickly removed, and sections of approximately 0.5 mm were made and divided in four groups.…”
Section: Ex Vivo Preparationmentioning
confidence: 99%
“…35 Briefly, male SpragueDawley rats were anesthetized and euthanized by decapitation. Kidneys were quickly removed, and sections of approximately 0.5 mm were made and divided in four groups.…”
Section: Ex Vivo Preparationmentioning
confidence: 99%
“…Although AVP is the major regulator of AQP2 trafficking and is the focus of this review, it must be emphasized that a variety of other molecules/hormones can influence AQP2 membrane accumulation and cellular expression, e.g., prostaglandins [87,115,130], bradykinin [107], dopamine [3], arginine/NO [4], ANP [47], oxytocin [9], and angiotensin II [56].…”
Section: Maintaining Body Water Balancementioning
confidence: 99%
“…Although membrane abundance of AQP2 is mainly under vasopressin control, it has also been shown that the cell surface expression of AQP2 might be tightly modulated by the synergic activity of various small molecules and hormones such as PGE2 [8,9], bradykinin [10], dopamine, ATP [11] and ANP [12]. Importantly, signal pathways controlled by these agonists are often associated with a profound reorganization of the actin cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%